Unpacking visitors' experiences at dark tourism sites of natural disasters. (October 2021) - Zhang, Yachen
Abstract: Visiting post-natural disaster sites has been burgeoning in recent years. Dark tourism at those settings has been utilised as part of relief and recovery strategies after natural disasters. This research, undertaken at four post-natural disaster sites, explores the onsite experience of 196 participants using semi-structured interviews and participant-generated photos. Findings indicate that experiencing a disaster context could be cognitive, emotional, introspective, sensory, relational and hedonic. Some experience dimensions, such as introspective and relational experiences, might help illuminate the value of promoting dark tourism at natural disasters. Experience discrepancy across multiple cases indicates the heterogeneity and malleability of visitors' experiences in the context. By depicting lived experiences of tourists, this study contributes to the understanding of the ways through which dark tourism sites at natural disasters are experienced and constructed as well as provides practical insights into tourist experience creation. Highlights: Experiences at natural disaster dark sites could be cognitive, emotional, introspective, sensory, relational and hedonic. Introspective and relational experiencesmight illuminate the value of promoting dark tourism at natural disasters. Experience discrepancy across multiple cases indicates the heterogeneity and malleability of dark tourism experiences.